O033 Video tuition of intracavernosal alprostadil injection for management of erectile dysfunction. (22nd July 2022) - Śluzar, P; MacAskill, F; Gordon, P; Briggs, K; Sandher, A; Hewson, S; Barron, E; Yap, T; Eardley, I; Shabbir, M
Abstract: Introduction: Intracavernosal injections (ICI) are the second line treatment of erectile dysfunction (ED). To reduce the risk of complications, primarily priapism, the first administration has traditionally required face-to-face appointments. With a move to remote working, the safety and feasibility of an instructional video for the first self-administration of ICI was assessed. Methods: Two centres recruited patients, with participants receiving a pack comprising a written instruction leaflet and a Viridal Duo prescription, followed by an email with our instructional video. Patients were given a specific time to self-administer their ICI (Alprostadil 2.5 micrograms), when our CNS was available for support. The same CNS would follow up two hours later via telephone to assess the experience using a Likert scale semi-structured interview. Results: Thirty-nine patients were recruited between two centres, with 35 continuing to injection. The median age was 63 years (range 34–78). The most common ED aetiology was post-prostatectomy (18/35). Thirty-four (97%) recruits found the video instructions clear, with it being watched a mean 2 (range 1–8) times. Only 1 patient (3%) required telephone support. At the 2.5mcg dose, the mean erection hardness score was 2 (range 1–4) after an average of 5 minutes. No patients reported significant bruising at the injection site and there was no priapism. Thirty-three patients (94%) were very or extremely likely to recommend this method for starting ICI therapy. Conclusion: Our study shows ICI tuition does not require direct supervision, thereby reducing face-to-face contact and will tackle significant waiting lists by increasing productivity. Take-home message: Our study shows ICI tuition does not require direct supervision, thereby reducing face-to-face contact and will tackle significant waiting lists by increasing productivity.